Optimal parenting with present-biased children - Goh, Fang Ru (2017)
This paper develops a game-theoretical model between an altruistic parent and a present-biased child in deciding on the amount of effort towards education. Our model posits that the degree of present bias leads to a divergence between the parent and child’s effort. Our results establish that a child’s human capital accumulation is increasing in parental control and decreasing in present bias. Additionally, there exists the strategic effect of the parental effort where a higher level of efforts are invested when the child is present-biased. We also observe that the optimal parenting strategy is to exert a high control over the child when they are young. Our model is potentially useful in explaining the effectiveness of parental control in a child’s accumulation of human capital. It can explain the phenomenon of the academic success of the Asian students, where there is a culture of high parental control. It is also especially useful for developing countries to realise the importance of intervention for children’s education, especially when they are young. Allocating more educational resources in early childhood education may help to accumulate human capital more effectively in a country.